COURSE SYLLABUS: RESPONDING TO STUDENTS’ NEEDS IN THE FOURTH INDUSTRIAL REVOLUTION - Firima Zona Tanjung (IJIET (International Journal of Indonesian Education and Teaching), 2019)
Universities are required to improve their service mainly in offering effective reading course which meets diverse issues. Reading course syllabus should be designed appropriately dealing with the students’ needs and the shift of current global issues. This study was carried out in the purpose of evaluating pre-existing reading course syllabus and intending the novel one. The study utilized various methods namely questionnaire, interview, and documents. The data were analyzed statistically and descriptively. It was found that students focus on the general- literary skills mastery only so they have unclear goals in the content-specific literary skills. Given that findings, backward design was employed. Skill syllabus and content-based syllabus are selected to promote students’ skills in their contextual learning. Integration of contextual and flexible topics, materials, and mobile apps in the course syllabus is significant to transform their learning to be more fruitful.